Evaluating the Effectiveness of a Cloud Computing-Based LMS in Developing Learning Skills in Accounting Major - Choms Gary Ganda Tua Sibarani; Tri Effiyanti; Jabal Ahsan (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to evaluate the factors influencing student acceptance and satisfaction with SIPDA, a cloud-based Learning Management System (LMS), among accounting majors at the Faculty of Economics, Universitas Negeri Medan. Methodology: A quantitative research design was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS. The study involved 213 accounting students from both regular and non-education programs, selected through a total sampling approach. Data were collected using structured questionnaires that measured five core constructs: instructor quality, content quality, perceived usefulness, satisfaction, and self-regulation. The collected data were analyzed using SEM-PLS to test the hypothesized relationships and assess model validity and reliability. Main Findings: Of the seven hypotheses tested, six were found to be positive and statistically significant. Instructor and content quality had strong positive effects on perceived usefulness and satisfaction, while perceived usefulness significantly enhanced satisfaction. However, self-regulation showed an adverse indirect effect on satisfaction through perceived usefulness (β = -0.061), indicating that highly self-regulated students are more critical when the LMS fails to meet their expectations. The model demonstrated high predictive validity (R² = 0.790) and fulfilled all reliability and construct validity criteria. Novelty/Originality of this study: This study reveals a counterintuitive relationship between self-regulation and satisfaction. While self-regulation typically fosters positive outcomes, students with greater autonomy and digital literacy are dissatisfied when LMS responsiveness and personalization are lacking. The findings emphasize the need for adaptive, learner-centered LMS designs tailored to self-regulated learners in higher education.